2011
DOI: 10.1063/1.3535191
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric effect and critical exponents of Fe77Co5.5Ni5.5Zr7B4Cu1: A detailed study

Abstract: The critical exponents of the alloy have been determined with the Kouvel–Fisher method to predict the field dependence of the magnetic entropy change ΔSM. The nonlinear fit of ΔSM(H) to a power law provides a field exponent in perfect agreement with the predictions of the relevant scaling laws using the obtained critical exponent values. It is shown that possible discrepancies between these two methods for determining the field dependence of ΔSM might arise due to a poor resolution in the temperature of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…5, an increase of the exponent n peak with the increase of the standard deviation can be observed. From this plot, the exponent n peak of the MA sample leads to a maximum value for r $ 60 K. However, as the resolution in the determination of T peak has been 5 K, that might imply a measured value of n peak larger than the actual one [19], leading to an overestimation of r. In fact, which exhibits the best agreement among our analysis. This value of r can be related with a variation of B content of approximately 1 at.…”
Section: Resultssupporting
confidence: 45%
“…5, an increase of the exponent n peak with the increase of the standard deviation can be observed. From this plot, the exponent n peak of the MA sample leads to a maximum value for r $ 60 K. However, as the resolution in the determination of T peak has been 5 K, that might imply a measured value of n peak larger than the actual one [19], leading to an overestimation of r. In fact, which exhibits the best agreement among our analysis. This value of r can be related with a variation of B content of approximately 1 at.…”
Section: Resultssupporting
confidence: 45%
“…Previous studies on some Fe-based amorphous alloy ribbons also revealed the same result [8,19,20]. Very few works have found exponent values associated with longrange FM interactions [21,22] (see Table 1). Recently, with simple models of magnetism, Skomski has showed that long-range FM interactions could be established in complicated spin structures, including FM, anti-FM and non-collinear magnetic materials [23].…”
Section: Resultssupporting
confidence: 60%
“…The exponents belong to other universality classes if 1 2 < σ < 2. Additionally, depending on the nature and structure of alloy ribbons (i.e., amorphous and/or nanocrystals embedded in an amorphous host) [10,21,22], long-and short-range magnetic interactions may coexist.…”
Section: Resultsmentioning
confidence: 99%
“…7) and, in fact, MCE can be used as a tool to explore the fundamental physics in very different systems such as superconducting materials 18 or graphene. 19 However, several factors can yield an incorrect determination of n. Some of them can arise from experimental aspects, such as experimental indetermination of T C , 20 or the use of a sample with a non negligible demagnetizing factor, N D . 21,22 Both effects lead to artificial field dependencies of n at T C .…”
mentioning
confidence: 99%
“…In the former case, n(T C ) tends asymptotically to the correct value as the magnetic field increases in the range of the experimentally available values. 20,23 In the latter case, the raw data can be corrected from the effect of the demagnetizing field if N D is known, 21,22 using the following expression:…”
mentioning
confidence: 99%